The risk of atopic dermatitis in post-term gestational age at Sanglah Hospital Denpasar: A preliminary study - Made Ardinata; Ketut Dewi Kumara Wati; Wayan Dharma Artana; Hendra Santosa; Komang Ayu Witarini (DiscoverSys Inc., 2019)
Backgrounds: Several studies reported that Atopic Dermatitis (AD) increases with gestational age. Prolong dominancy of Th2 activity during gestation might contribute to the risk of atopic disease in infancy or beyond the period. This study aimed to evaluate the risk AD in post-term gestational age.Methods: A prospective observational study was conducted among 73 living births at Sanglah Hospital Denpasar from December 2015 to January 2016 period. Infants were classified into 2 such as exposed (post-term) and non exposed (term and preterm) group. Parents-follow up by phone was carried out in 1 until 2 months interval. The study was finished once AD diagnosed, subject died or lost to follow up. Statistical analysis was carried out using SPSS ver. 20 software whereas P-value > 0.05 was considered significant.Results: About 20 (233%) infants were preterm, 36 (49.3%) a term, and 17 (23,3%) post-term. The median value of follow up duration was 28 (14-35) days. Based on AD, there were total 24 cases which divided into 15(62.5%), 8(33.3%) and 1(4.17%) cases of AD in post-term, aterm, and preterm respectively. The incidence rate of AD in post-term was 88.2% while in non-post-term the incidence rate was 16.1%. The relative risk (RR) of AD in post-term was 5.47 (95% CI 2.94-10.23; P = 0.001)Conclusion: Post-term is 5.47 times more likely to develop AD compared with aterm and preterm infant. In addition, the incidence rate of AD in post-term infant was 88.2% at Sanglah Hospital Denpasar